1994–2004: 10 years of research on the anaerobic oxidation of ammonium. (1st February 2005) - Jetten, M.S.M.; Cirpus, I.; Kartal, B.; van Niftrik, L.; van de Pas-Schoonen, K.T.; Sliekers, O.; Haaijer, S.; van der Star, W.; Schmid, M.; van de Vossenberg, J.; Schmidt, I.; Harhangi, H.; et al.
Abstract : The obligately anaerobic ammonium oxidation (anammox) reaction with nitrite as primary electron acceptor is catalysed by the planctomycete-like bacteria Brocadia anammoxidans, Kuenenia stuttgartiensis and Scalindua sorokinii . The anammox bacteria use a complex reaction mechanism involving hydrazine as an intermediate. They have a unique prokaryotic organelle, the anammoxosome, surrounded by ladderane lipids, which exclusively contains the hydrazine oxidoreductase as the major protein to combine nitrite and ammonia in a one-to-one fashion. In addition to the peculiar microbiology, anammox was shown to be very important in the oceanic nitrogen cycle, and proved to be a very good alternative for treatment of high-strength nitrogenous waste streams. With the assembly of the K. stuttgartiensis genome at Genoscope, Evry, France, the anammox reaction has entered the genomic and proteomic era, enabling the elucidation of many intriguing aspects of this fascinating microbial process.